The Great Caf and Orchestra, Old Faithful Inn, Union Pacific System, Yellowstone Park (Cardinell-Vincent Co. Pub.)
On verso: In the Zone at the Panama-Pacific International Exposition, San Francisco, on 4 1/4 acres, the Union Pacific System portrays the most important features of Yellowstone National Park. Among these Old Faithful Geyser, true to life, throws heaven ward great volumes of steam and water every 63 minutes. Beyond question Old Faithful Inn-seating 2000- is the grand cafe de luxe of the Exposition. The official orchestra of 80 skilled musicians here gives daily concerts.